Redescription of Chusquea perligulata (Poaceae: Bambusoideae: Bambuseae: Chusqueinae) and description of a similar but new species of Chusquea from Ecuador - Clark, Lynn G.; Mason, Jessica J. (Phytotaxa, 2019)
The poorly known but distinctive Chusquea perligulata, which was originally described from vegetative material and tentatively placed in Guadua, is completely described and illustrated, and its basionym is neotypified. As its name suggests, C. perligulata has well developed inner ligules (1–) 2–10 cm long on the foliage leaves. This species is endemic to Ecuador, as is a morphologically similar species described here as C. jorgemoranii. This species is distinguished from C. perligulata by a combination of features including abaxially hispid culm leaves lacking differentiation between the sheath and the blade, a dome-shaped central bud, shorter inner ligules, smaller synflorescences and slightly larger spikelets. Chusquea jorgemoranii is illustrated and compared with C. perligulata. Both species are classified within Chusquea sect. Verticillatae.